2014
DOI: 10.3945/jn.114.196436
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Are Absorbed in Biologically Meaningful Amounts from Nutritionally Relevant Doses of Cow Milk and Affect Gene Expression in Peripheral Blood Mononuclear Cells, HEK-293 Kidney Cell Cultures, and Mouse Livers

Abstract: We conclude that miRNAs in milk are bioactive food compounds that regulate human genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
523
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(550 citation statements)
references
References 41 publications
17
523
3
2
Order By: Relevance
“…Human-milk-derived mEVs have been shown to modulate the functionality of immune cells [12,31]. Similar to human mEVs, bovine mEVs may have a biological function, as described previously [16]. It is possible that mEVs from bovine milk can be used as an immunomodulatory agent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Human-milk-derived mEVs have been shown to modulate the functionality of immune cells [12,31]. Similar to human mEVs, bovine mEVs may have a biological function, as described previously [16]. It is possible that mEVs from bovine milk can be used as an immunomodulatory agent.…”
Section: Discussionmentioning
confidence: 96%
“…In the previous report, mEVs were internalized into human macrophage cells [15]. Another report demonstrated that mEVs from bovine milk deliver biologically functional miRNA into human cells and affect gene expression of recipient cells [16]. From these results, mEVs are useful DDS for the delivery of nucleic acid medicine, such as miRNA and siRNA.…”
Section: Discussionmentioning
confidence: 97%
“…61 Similarly to human breast feeding, the consumption of raw bovine milk is also associated with decreased risk of allergy and asthma, 62 and it cannot be excluded that bovine miRNAs are implicated in these phenomena. A recent study proved that bovine milk-derived miRNAs can be absorbed and appear in human blood after milk consumption, 63 but this finding is also debated. 64,65 The bovine milk-derived xeno-miRNA, miR-29b which is identical to its human counterpart, 66 has been shown to raise the expression of the runt related transcription factor 2 (RUNX2) in human blood peripheral mononuclear cells.…”
Section: Dietary Xeno-mirna In Inter-species Communicationmentioning
confidence: 99%
“…64,65 The bovine milk-derived xeno-miRNA, miR-29b which is identical to its human counterpart, 66 has been shown to raise the expression of the runt related transcription factor 2 (RUNX2) in human blood peripheral mononuclear cells. 63 As RUNX2 is involved in the regulation of bone homeostasis by inducing osteoblasts and inhibiting the osteoclast differentiation in the host, the ingested bovine miR-29b xeno-miRNA might be hypothesized to induce bone mineralization. 67,68 Milk consumption might thus promote bone mineralization not only as a classical source of dietary calcium, but even via its miRNA content.…”
Section: Dietary Xeno-mirna In Inter-species Communicationmentioning
confidence: 99%
“…Focusing on mammals exposed to plants and milk (Dickinson et al 2013;Snow et al 2013;Witwer et al 2013;Baier et al 2014;Tosar et al 2015), experimental results and current understanding of RNA stability, transport, and function do not appear to be consistent with proposed forms of cross-kingdom communication. In many cases, presumably positive ncRNA findings were shown to result from, e.g., sample contaminations or artefacts caused by technical limitations of the applied technologies (Witwer 2015).…”
Section: Kenneth W Witwer Johns Hopkins University School Of Medicimentioning
confidence: 99%